PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL, DAN SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Novita Sari Dewi Tandiawan; Jonnardi Jonnardi (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This study aims to determine the effect of profitability, liquidity, and capital structure on the value of the firm with interest rates as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange. The method of determining the sample was by scanning sampling, the number of samples obtained was 34 companies in the mining sector. The random Effect Model was used for this research using Eviews application version 9.0. Research result indicates that liquidity has a significant positive effect on the firm’s value, while profitability and capital structure has no significant effect on the firm’s value, interest rates as a moderating variable also has no proof in moderating the relationship between capital structure and value of the firm.